2019
DOI: 10.1038/s41598-019-43513-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute-on-chronic liver disease enhances phenylephrine-induced endothelial nitric oxide release in rat mesenteric resistance arteries through enhanced PKA, PI3K/AKT and cGMP signalling pathways

Abstract: Acute-on-chronic liver disease is a clinical syndrome characterized by decompensated liver fibrosis, portal hypertension and splanchnic hyperdynamic circulation. We aimed to determine whether the alpha-1 agonist phenylephrine (Phe) facilitates endothelial nitric oxide (NO) release by mesenteric resistance arteries (MRA) in rats subjected to an experimental microsurgical obstructive liver cholestasis model (LC). Sham-operated (SO) and LC rats were maintained for eight postoperative weeks. Phe-induced vasoconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 76 publications
(111 reference statements)
5
11
0
Order By: Relevance
“…Previous works from our group have demonstrated that the mesenteric vasculature, especially superior mesenteric artery, plays a pivotal role in the maintenance of peripheral resistance through the release of vasodilators, such as NO [8]. Although alterations in blood pressure have been linked with modifications in smooth muscle sensitivity to NO [6,47], we found no differences in the vasodilator response to NO donor DEA-NO among our experimental groups, allowing us to rule out this possibility.…”
Section: Discussionmentioning
confidence: 45%
“…Previous works from our group have demonstrated that the mesenteric vasculature, especially superior mesenteric artery, plays a pivotal role in the maintenance of peripheral resistance through the release of vasodilators, such as NO [8]. Although alterations in blood pressure have been linked with modifications in smooth muscle sensitivity to NO [6,47], we found no differences in the vasodilator response to NO donor DEA-NO among our experimental groups, allowing us to rule out this possibility.…”
Section: Discussionmentioning
confidence: 45%
“…Animals were randomly divided into two groups: Shamoperated (SO; n = 17), in which the common bile duct was dissected; and MHC (n = 17), in which the extrahepatic biliary tract was resected (García-Moreno et al, 2005;Sastre et al, 2016b;Gilsanz et al, 2017;Caracuel et al, 2019). Surgery was performed under aseptic but not sterile conditions.…”
Section: Animalsmentioning
confidence: 99%
“…Systolic blood pressure (SBP) was measured using the tail-cuff method 8 weeks after the surgery was performed (Xavier et al, 2010;Sastre et al, 2016b;Caracuel et al, 2019).…”
Section: Systolic Blood Pressurementioning
confidence: 99%
See 2 more Smart Citations